(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study compared the effect of lecture method and multiple instructional approach on students’ cognitive achievement in basic technology. Two research questions were answered and two null hypotheses were tested at 0.05 level of significance. Quasi-experimental design was adopted for the study, specifically, the non-equivalent control group design. The study was carried out in Ilesa Education Zone of Osun State. The population of the study was 1,876 JSS two students, while the sample comprised 80 JSS two students drawn from two intact classes in two junior secondary schools in Ilesa. Experimental group was taught using multiple instructional approach, while the Control group was taught using lecture method. The treatment lasted for four weeks after pretest has been administered using Basic Technology Achievement Test (BTAT) as instrument for data collection. The instrument was subjected to face and content validity. Test-retest method was adopted to establish reliability of the instrument which yielded a coefficient of 0.75. Data collected were analyzed with mean and analysis of covariance (ANCOVA). The result revealed that students taught with multiple instructional approach performed better than students taught with lecture method in basic technology. There was no significant difference in the mean scores of male and female students in basic technology after the treatment. Based on the findings of the study, it was recommended that relevant agencies should instruct basic technology teachers to adopt multiple instructional approach when teaching to enhance students’ cognitive achievement.